Knowledge transfer in cross-border post-acquisition integration - Ussa, Heidi (My University, 2019)
This study examines effective knowledge transfer in post-acquisition integrations. Although research already exists on knowledge transfer, significant gaps could be found in the literature, especially in the context of cross-border acquisition integrations. The aim of this study is to identify how can knowledge be transferred effectively in cross-border acquisition integrations. The sub-questions of this thesis are to find out why effective knowledge transfer is vital in integrations; what characteristics influence the transfer of knowledge and which transfer mechanisms should be chosen to ensure effective knowledge transfer. In order to attain the aim of this study, a framework was conducted based on the existing theories and findings of earlier literature. The theoretical framework combined knowledge transfer with different integration measures. Based on the theoretical framework and operationalization table, six expert interviews were conducted during three weeks in February 2019. The interviewees were chosen based on their expertise in the subject. All of the interviews were transcribed and analyzed through thematic analysis. Based on the transcribed interview material, thematic networks were built to be used for the analysis of this study. The empirical research of this study reinforced the existing theories to a large extent but gave also new viewpoints on the factors influencing effective knowledge transfer. It was concluded that knowledge transfer is an important element of integrations and depending on the level of the integration, significant amount of knowledge must be transferred in the integrations. If the transfer of knowledge is not effective or encounters challenges, it can affect the entire acquisition integration outcome. Consistent and clear communication is vital in order to build trust and a beneficial relationship between the acquisition parties. The better the communication achieved is, the more knowledge is transferred. Communication was concluded to be of great importance especially in the context of cross-border post-acquisition integration. Furthermore, surveillance is added to the influence factors to be an important aspect, since integrations often involve uncertainty among the employees. This uncertainty can also be decreased by effective communication. Additionally, building social communities to transfer knowledge, especially tacit one, is highlighted to be an effective mean. However, one should not merely rely on one transfer mechanism as the most effective way is often times a combination of more than one. Future research is encouraged to be able to gain more insight on this topic.
Keywords: knowledge transfer, post-acquisition integration